Systematic Engineering of Single Substitution in Zirconium Metal-Organic Frameworks toward High-Performance Catalysis. - Huang, Ning; Yuan, Shuai; Drake, Hannah; Yang, Xinyu; Pang, Jiandong; Qin, Junsheng; Li, Jialuo; Zhang, Yingmu; Wang, Qi; Jiang, Donglin; Zhou, Hong-Cai (Journal of the American Chemical Society, 2017)
Zirconium-based metal -- organic frameworks (Zr-MOFs) exhibit great structural tunability and outstanding chemical stability, rendering them promising candidates for a wide range of practical applications. In this work, we synthesized a series of isostructural PCN- 224 analogues functionalized by ethyl, bromo, chloro, and fluoro groups on the porphyrin unit, which allowed us to explicitly study the effects of electron-donating and electron-withdrawing substituents on catalytic performance in MOFs. Owing to the different electronic properties of ethyl, bromo, chloro, and fluoro substitutes, the molecular-level control over the chemical environment surrounding a catalytic center could be readily achieved in our MOFs. To investigate the effects of these substitutes on catalytic activity and selectivity, the oxidation of 3-methylpentane to corresponding alcohols and ketones was utilized as a model reaction. Within these five analogues of PCN- 224, an extremely high turnover number of 7680 and turnover frequency of 10 240 h was achieved by simply altering the substitutes on porphyrin rings. Moreover, a remarkable 99% selectivity of the tertiary alcohol over the five other possible byproducts are realized. We demonstrate that this strategy can be used to efficiently screen a suitable peripheral environment around catalytic cores in MOFs for catalysis.